2014
DOI: 10.2306/scienceasia1513-1874.2014.40.125
|View full text |Cite
|
Sign up to set email alerts
|

Development of a defined starter culture mixture for the fermentation of sato, a Thai rice-based alcoholic beverage

Abstract: Sato is a traditional Thai alcohol beverage produced by the fermentation of steamed rice with a microbial starter. The industrial production of sato faces problems with inconsistent quality due to the variability in the microbial community of the starter. Previously, an NP1 starter was selected from 114 starter samples for its abilities to liquefy rice, to ferment and produce ethanol, and to give a good flavour and taste to the resultant sato. Here, we developed a defined starter culture mixture for sato ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…1). Likewise, the fermented rice sap from purple plain rice was previously reported to inhibit mushroom tyrosinase activity (30). In this study, the FUBRS showed an inhibitory effect on tyrosinase activity (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…1). Likewise, the fermented rice sap from purple plain rice was previously reported to inhibit mushroom tyrosinase activity (30). In this study, the FUBRS showed an inhibitory effect on tyrosinase activity (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The number of isolated yeasts was varied from 1 to 10 7 CFU/g-starter. These members were close to those reported by Limtong et al (2002) and Luangkhlaypho et al (2014). The ethanol and ester production by (1) amylolytic yeasts (2) alcoholic yeasts and (3) aromatic yeasts were compared (Table 1).…”
Section: Screening Of Alcoholic Yeasts and Aromatic Yeastssupporting
confidence: 87%
“…The nature of microbial communities in Cambodian traditional starters, their interactions, and their contributions to the synthesis of aromas during fermentation are still widely unknown. Microbial diversities in fermentation starters have been studied by many researchers [5,6,7,8,9,10,11,12,13]. However, there is a very limited number of studies exploiting the interaction between these three groups of microorganisms and their effect on rice wine quality during the fermentation process.…”
Section: Introductionmentioning
confidence: 99%